Strategi Komunikasi Organisasi dalam Upaya Meminimalisir Konflik Senioritas pada Pengurus Ranting Fatayat Nu Desa Parakanmanggu - Isyfi Agni Nukhbatillah; Ai Robihatil Milah; Misbahhudin Misbahhudin; Ahmad Hapidin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
Students' interest in reading in Indonesia is still relatively low, so reading literacy or fostering interest in reading in schools is very well implemented. This research aims to identify the strategies used by the principal of SMAN 1 Langkaplancar to increase students' interest in reading. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews. The research results showed that the school principal used several strategies such as school literacy programs, improving library facilities, collaborating with regional libraries, and involving the community in literacy activities. These strategies have proven effective in increasing students' reading interest. Factors such as principal leadership, teacher and parent support, adequate facilities, and community involvement are key to the success of this program. By continuing to develop and expand literacy programs, it is hoped that students' interest in reading can continue to be increased thereby contributing to improving the quality of education in schools. Improving library facilities is an important part of the principal's strategy to increase students' interest in reading. At SMAN 1 Langkaplancar, various efforts to improve library facilities have succeeded in creating an environment that supports literacy activities and encourages students' interest in reading.